The Interactions Between Three Typical PPCPs and LDH - Li, Erwei; Liao, Libing; Lv, Guocheng; Li, Zhaohui; Yang, Chengxue; Lu, Yanan (Frontiers in Chemistry, 2018)
With a positively charged layered structure, layered double hydroxide has potential applications in remediation of anionic contaminants, which has been a hot topic for recent years. In this study, a Cl type Mg-Al hydrotalcite (Cl-LDH) was prepared by a co-precipitation method. The adsorption process of three pharmaceuticals and personal care products (PPCPs) (tetracycline (TC), diclofenac sodium (DF), chloramphenicol (CAP)) by Cl-LDH was investigated by X-ray diffraction (XRD), Zeta potential, dynamic light scattering (DLS), BET, FT-IR spectroscopy and molecular dynamics simulation. The results showed that the adsorption equilibrium of TC and DF could be reached in 120 min, and the maximum adsorption capacity of the Cl-LDH for TC and DF were 1.85 mmol/g and 0.95 mmol/g, respectively. The adsorption isothermal of TC was fitted with the Freundlich adsorption model, and the adsorption isothermal of DF was fitted with the Langmuir adsorption model. The adsorption dynamics of TC and DF followed the pseudo-second-order model. The adsorption mechanisms of the three PPCPs onto Cl-LDH were different based on the experimental results and molecular dynamics simulation. The TC adsorption on Cl-LDH was mainly driven by the electrostatic interactions between the negative charge of TC and the positive charge of Cl-LDH. The uptake of anionic DF was attributed both to ion exchange of DF for Cl- and the electrostatic interaction between the negatively charged DF and the positively charged structure layer of Cl-LDH. Cl-LDH does not adsorb the neutral CAP due to no electrostatic interaction. The molecular dynamic simulation further confirmed different configurations of the three selected PPCPs in the interlayer of Cl-LDH, which were responsible for the different uptake process of PPCPs on Cl-LDH.